2020
DOI: 10.1089/mab.2020.0029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hypothesis for Original Antigenic Sin in the Severe Disease of SARS-CoV-2 Infection

Abstract: In this hypothesis, we address the biological/immunological pathway leading to severe disease or death after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The underlying immune response is described with ''original antigenic sin'' (OAS) whereby previous infections influence the response to future virus encounters. We cite evidence for OAS-induced immunopathology in HIV-1 disease. We hypothesize that similar immune abnormalities can occur after infection with SARS-CoV-2. This hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Therefore, combining IgM and IgG serology testing may not provide much diagnostic value during the later stages of the disease, questioning the rationale for measuring IgM antibodies. In addition, the early appearance of anti-SARS-CoV-2 IgG antibodies is interesting to note as similar studies have reported detectable responses as early as 3-5 days post-infection [32,50,51]. Usually, early detection of specific IgG antibodies is expected in secondary immune responses when there is a memory to cross-reactive antigens from a previous infection with a coronavirus [52,53].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, combining IgM and IgG serology testing may not provide much diagnostic value during the later stages of the disease, questioning the rationale for measuring IgM antibodies. In addition, the early appearance of anti-SARS-CoV-2 IgG antibodies is interesting to note as similar studies have reported detectable responses as early as 3-5 days post-infection [32,50,51]. Usually, early detection of specific IgG antibodies is expected in secondary immune responses when there is a memory to cross-reactive antigens from a previous infection with a coronavirus [52,53].…”
Section: Discussionmentioning
confidence: 87%
“…Usually, early detection of specific IgG antibodies is expected in secondary immune responses when there is a memory to cross-reactive antigens from a previous infection with a coronavirus [52,53]. A phenomenon known as the "original antigenic syndrome" has been suggested to explain the underlying immune response in SARS-CoV-2, where previous infections influence the response to future virus encounters [50]. The early IgG response is possibly a memory response from earlier coronavirus infection, producing cross-reactive antibodies that do not have neutralizing potency [52].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly essential in novel viral infections, such as SARS-CoV-2 in which a pre-existing immunity is not possible ( Pichlmair and Reis e Sousa, 2007 ; Ayegbusi et al, 2018 ; Costela-Ruiz et al, 2020 ). The acute nature of the infection may also account for the possibility of severe re-infection due to its deceptive imprinting ( Kohler and Nara, 2020 ; Westerhuis et al, 2020 ). Deceptive imprinting refers to immune evasion mechanisms by certain viruses in which antibodies are mounted against immunodominant epitopes, thereby inducing strain-specific immunity, which offers little or no neutralization activity between serotypes and subtypes.…”
Section: Pathogenesis Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…(1,2) The finding that common cold cross-reacting antibodies are not neutralizing SARS-CoV-2 (3) have been discussed earlier with respect to the symmetrical network hypothesis. (4) A variety of therapeutic strategies have been used with limited effectiveness. (5) Thus, it is imperative to better understand the pathology and to find new medicines and improve currently used therapeutics.…”
Section: Introductionmentioning
confidence: 99%